Upaya Perlindungan Hukum Secara Terpadu Bagi Calon Tenaga Kerja Indonesia pada PT Trias Insan Madani Kota Depok - Imam, Muhamad; Untari, Kurnia Sri; Pambudi , S Untung; Haidi, Nasrul; Nurhayati, Nurhayati; Rahmawati, Yenny; Alfurcaan, Reynaldi; Simanungkalit, Dohma P Nathanael; Sutrisno, Andri (CV. Era Digital Nusantara, 2024)
Students from the IBLAM College of Law who were carrying out KKN coursework were accompanied by Lecturer Andri Sutrisno, S.H., M.H., M.Sos., and also attended by Mrs. Dewic Sri Ratnaning Dhumillah, S.H., M.H., as a resource person from the IBLAM Campus and also Mr. Japar Malik, S.E., M.Sc., as a resource person from the Indonesian Ministry of Manpower carried out Legal Outreach and Education related to Legal Protection Efforts for prospective Indonesian Migrant Workers (TKI) at PT. Trias Insan Madani Depok City. Legal protection efforts for prospective Indonesian Migrant Workers (TKI) are an important issue, especially in ensuring that their rights are protected from before departure until they return to their homeland.